2019
DOI: 10.4047/jap.2019.11.6.331
|View full text |Cite
|
Sign up to set email alerts
|

A new method to measure the accuracy of intraoral scanners along the complete dental arch: A pilot study

Abstract: PURPOSEThe purpose of this study is to assess the accuracy of three intraoral scanners along the complete dental arch and evaluate the feasibility of the assessment methodology for further in vivo analysis.MATERIALS AND METHODSA specific measurement pattern was fabricated and measured using a coordinate measuring machine for the assessment of control distances and angles. Afterwards, the pattern was placed and fixed in replica of an upper jaw for their subsequent scans (10 times) using 3 intraoral scanners, na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 37 publications
(72 reference statements)
2
6
0
Order By: Relevance
“…These findings are comparable with previous investigations [3,10]. However, the total deviations for the Trios 3 Pod and the Primescan in this clinical study were higher compared with the laboratory data reported by Ender et al [9] and Iturrate et al [33]. This could be due to different evaluation methods (percentiles) and furthermore explained by the in vivo conditions and the presence of saliva, oral structures, and patient movement(s) that may influence accuracy [34][35][36].…”
Section: Discussionsupporting
confidence: 88%
“…These findings are comparable with previous investigations [3,10]. However, the total deviations for the Trios 3 Pod and the Primescan in this clinical study were higher compared with the laboratory data reported by Ender et al [9] and Iturrate et al [33]. This could be due to different evaluation methods (percentiles) and furthermore explained by the in vivo conditions and the presence of saliva, oral structures, and patient movement(s) that may influence accuracy [34][35][36].…”
Section: Discussionsupporting
confidence: 88%
“…Mizumoto et al [ 75 ] in a recent in vitro study have reported that in the completely edentulous maxilla with 4 installed implants, including scanning data from the palate did not result in statistically significant higher accuracy. In an effort to minimize discrepancies when scanning edentulous sites among multiple implants, Iturrate et al [ 76 , 77 ] have investigated the in vitro effectiveness of using an auxiliary geometric device (AGD) firmly attached onto the implant scanbodies. The authors reported statistically significantly higher accuracy when the AGD was used regardless of the IOS scanner tested.…”
Section: Resultsmentioning
confidence: 99%
“…Because it is not possible to use machines with certified accuracy such as CMMs, articulated arms or industrial scanners in the patient’s mouth, and having a certified reference file is not possible, measuring the trueness of optical impressions with IOS in vivo is difficult [ 2 , 4 , 18 ]. Some authors have recently tried to introduce indexes [ 19 , 20 ] or geometric shapes with known dimensions (custom measuring aids) [ 21 , 22 ] in the mouth to evaluate the distortions affecting the optical impression in vivo, but the vast majority of studies of the trueness of IOSs have been made in vitro on plaster models [ 14 , 15 , 23 26 ].…”
Section: Introductionmentioning
confidence: 99%